Evaluasi Program Kerja Balai Latihan Kerja (BLK) Komunitas Pondok Pesantren Ansharullah Kabupaten Kampar - Malasari, Nur; Abdul Sadad (Journal of Research and Development on Public Policy, 2023)
Presidential Regulation of the Republic of Indonesia No. 68 of 2022 concerning the revitalization of vocational education and training explains the importance of providing effective training so as to produce graduates who are competent and needed by the job market and able to become entrepreneurs. BLK Komunitas Ansharullah is one of the training institutions that organizes information technology vocational job training programs in Kampa District. The purpose of this study is to evaluate the work program of BLK Komunitas Ponpes Ansharullah and the obstacles faced in the work program of BLK Komunitas Ponpes Ansharullah. The theory used by the research is the CIPP evaluation model developed by Daniel Loyer Stufflebeam 1985 there are 4 evaluations, namely context, input, process and Product. The novelty of this research adds evaluation aspects, namely Outcome and Benefit. This study used qualitative descriptive research methods, data collection techniques through observation, interviews, and documentation. Data analysis used is data collection, data reduction, data presentation and conclusions. The results showed that the evaluation of the BLK work program of the Ponpes Ansharullah Community in Kampa District can be continued but still needs improvement related to the preparation of work program mechanisms, funding sources, organizer performance and development efforts to increase the impact of training to produce competent and professional quality and quantity. The obstacles faced are the ineffective performance of the organizers, the source of funding for training programs is not clear and there is no innovation and work program development strategies related to training activities.